THE EFFECT OF INFLUENCER ATTRACTIVENESS AND EXPERTISE ON INCREASING PURCHASE INTENTION WITH BRAND IMAGE AS AN INTERVENING VARIABLE: (CASE STUDY OF CONSUMERS OF SCARLETT WHITENING PRODUCTS IN YOGYAKARTA CITY) - Dona Fitriani; Ida Bagus Nyoman Udayana; Lusia Tria Hatmanti Hutami (Journal of Management and Islamic Finance, 2023)
Recently, the beauty trend for face and body care has become more popular, this has been adopted in many rapidly growing beauty industries. The objective of this study is therefore to determine the influence of Attractiveness and Expertise Influencers, and of Brand Image on Purchase Intention. This research was quantitative by taking 100 samples of social media users in the city of Yogyakarta, men and women aged at least 15 years old who have seen the Scarlett Whitening Endorsement brand broadcasts on influencers on social media. The sampling method used a non-probability method and the sampling technique was purposive sampling. Data collection was done by sending a link to the questionnaire via Google From which was distributed online to respondents. Data analysis used IBM SPSS application. The results of this study indicate that the influence variable Attractiveness (X1) has a significant positive effect on brand image (Z) with a value of 0.004, then the Influencer expertise variable (X2) has a significant positive effect on brand image (Z) with a value of 0.000. The brand image variable (Z) has a significant positive effect on purchase intention (Y) with a value of 0.000. Moreover, the Attractiveness influence variable (X1) has no significant effect on purchase intention (Y) with a value of 0.168. The variable Expertise influence (X2) has a significant positive effect on purchase intention (Y) with a value of 0.001. In addition, the results of the study also show that brand image is able to act as an intervening variable for the influence of Attractiveness and Expertise influencers on the purchase intention of consumers of Scarlett Whitening products in the City of Yogyakarta.